The Effectiveness of Outseal Programmable Logic Controller-based Training Kit to Improve Vocational High School Students' Control System Skills - Setyawan, Herlin; Sukardi; Risfendra; Effendi, Hansi; Syahril (Universitas Pendidikan Ganesha, 2024)
The problem in this study is that many students still have not mastered the skills of PLC-based control systems in accordance with the learning objectives. This is because the learning media is only a simulation using buttons and pilot lights without using the original components. The aims of this study is to examine and reveal the effectiveness of the outseal PLC-based PLC training kit in improving students' practical skills in PLC-based control systems. Pre-experiment one group pre-test and post-test is the research methodology used in this study, with a research sample of 32 students from the electrical power installation engineering department vocational school. The research data were collected using a skill assessment questionnaire and analyzed using paired sample t-test analysis technique and effect size test. The results revealed that the t-value obtained was 7.915 with a significance of 0.000 and a value of d = 1.701. These results show differences in students' skills after and before using the training kit that is applied and proven to improve student skills significantly. Thus, it is proven that this training kit effectively improves vocational students' skills. Based on these results, vocational high schools are expected to apply this training kit to facilitate learning and improve students' PLC-based control system skills.